Large-Scale Quantitative Analysis of Sources of Variation in the Actin Polymerization-Based Movement of Listeria monocytogenes - Soo, Frederick S. (Biophysical Society, 2005)
During the actin polymerization-based movement of Listeria monocytogenes, individual bacteria are rapidly propelled through the host cell cytoplasm by the growth of a filamentous actin tail. The rate of propulsion varies significantly among individuals and over time. To study this variation, we used a high-throughput tracking technique to record the movement of a large number (∼7900) of bacteria in Xenopus frog egg extract. Most bacteria (70%) appeared to maintain an individual characteristic speed over several minutes, suggesting that the major source of variation in average speed is intrinsic to the bacterium. Thirty percent of bacteria had significant changes in speed over time spans of a few minutes, including 17% that appeared to collide with obstacles and 13% that moved with a significant periodic component. For the latter, the peak frequency was proportional to speed, suggesting a mechanism with a fixed spatial scale of ∼0.6 bacterial length. Near the rear of the bacterium, temporal fluctuations in actin density were positively correlated with fluctuations in speed, whereas near the front the correlation was negative. A comparison of the performance of linear models that predict motion given actin density suggests that the mechanism has a history of 5–10 s, and that fluctuations in actin density near the front of the bacteria contain more predictive information than the rear. Our results are consistent with physical models where bacterial speed is governed by the rate of dissociation of bonds between the bacterial surface and the actin tail, and individual variation is determined by long-lived intrinsic variability in bacterial surface properties.